2013
DOI: 10.1097/coc.0b013e3182467bb1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Microsurgical Resections for Repeated Recurrence of Glioblastoma Multiforme

Abstract: Microsurgical resection of repeatedly recurring GBM is likely to prolong survival. Repeated surgical resection may be considered as an effective treatment option in addition to radiochemotherapy in repeated GBM recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 66 publications
1
18
0
2
Order By: Relevance
“…Repeat resection for recurrent GBM has been shown to increase quality of life as well as length of survival. 1,6 However, Gorlia et al 3 (2012) show that performance status is the major prognostic factor when determining overall survival and progressionfree survival in patients with recurrent GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeat resection for recurrent GBM has been shown to increase quality of life as well as length of survival. 1,6 However, Gorlia et al 3 (2012) show that performance status is the major prognostic factor when determining overall survival and progressionfree survival in patients with recurrent GBM.…”
Section: Discussionmentioning
confidence: 99%
“…9 Likewise, the goal at repeat resection is the same-to achieve as extensive a resection as possible to decrease tumor burden, thereby improving overall patient survival time as well as quality of life. 1,6 Although MRI is the standard method of preoperative tumor detection, MRI alone may not be able to completely visualize the full extent of diffuse infiltrative glial tumors. In cases where there is a concern for diffuse tumor spread, supplemental techniques for tumor detection such as intraoperative 5-aminolevulinic acid (5-ALA) may be helpful in linking the recurrence to the primary site.…”
mentioning
confidence: 99%
“…Several retrospective Level of Evidence III-IV studies 74 support repeat tumor resections, as long as the patient's performance status is not low and preoperative tumor volume is not excessive. 1,5,16,26,30,55 A randomized, double-blind, placebo-controlled control trial also supported the implantation of carmustine (BCNU) wafers in tumor cavities after repeat operation. 10 Although salvage temozolomide had previously been used for recurrent GBM, 9,56,80 recent Level II evidence clinical studies in patients with recurrent GBM have demonstrated that salvage chemotherapy combining bevacizumab, an antiangiogenic agent, with cytotoxic drugs can extend progression-free survival and overall survival to 6.1 and 9.2 months, respectively.…”
Section: Treatment Of Recurrent Hggsmentioning
confidence: 99%
“…76 In select patients, salvage chemotherapy for recurrent HGGs is optimally preceded by repeat resection. 1,5,16,26,30,55,74,81 However, for a range of reasons, there are subsets of patients who are not ideal candidates for traditional open surgery, and many patients decline open surgery due to associated morbidity. For these patients, LITT has been considered a reasonable option for many reasons (Fig.…”
Section: Treatment Of Recurrent Hggsmentioning
confidence: 99%
“…In spite of the advances in microsurgery to accomplish optimized resections (extensive, without worsening of the neurologic function), followed by standard treatment with concomitant radiotherapy (RT) and chemotherapy (CT) and maintenance therapy with temozolomide (TMZ) 2 , the patients' survival remains rather limited, with small survival gains obtained in recent years 3,4,5 . The main factors associated with patient survival are age and functional status before surgery 6,7 ; the extent of resection 7,8 , adjuvant treatment 7,9 and methylation of the O6-methylguanine-DNA methyltransferase (MGMT) promoter 10 , which also seem to be associated with increased survival. The role of surgical treatment for recurrence or regrowth of GBM has not yet been fully established.…”
mentioning
confidence: 99%